Efektivitas Hukum Ekonomi Syariah dan Hukum Positif terhadap Transformasi Digital - Nurahmad Nurahmad; Darmawati H; Abdul Syatar (AHKAM, 2025)
This study is motivated by the limited research on the effectiveness of sharia economic law and positive law in responding to the rapid pace of digital transformation, particularly in providing legal protection and certainty for digital entrepreneurs in Indonesia. The aim of this research is to examine the extent to which these two legal systems are capable of effectively and sustainably regulating and responding to technological developments. The study employs a qualitative approach using socio-juridical and historical-normative designs. Data were collected through literature review of formal regulations, sharia fatwas, and expert interviews. The findings reveal that sharia economic law demonstrates a high degree of flexibility through approaches such as ijtihād, maṣlaḥah, and contemporary fatwas, including DSN-MUI Fatwa No. 117/2018 on information technology-based financing services. However, these fatwas do not yet carry binding legal force within the national legal system. Conversely, positive law offers stronger legal certainty through formal regulations such as the Electronic Information and Transactions Law (ITE Law), Financial Services Authority Regulation (POJK) No. 77/2016 on IT-Based Lending Services, and the Personal Data Protection Law (UU PDP), although it often lags in addressing emerging technologies such as blockchain and smart contracts. The study concludes that sharia economic law excels in ethical values and social benefit orientation, while positive law is stronger in terms of legal structure and formal sanctions. The implications of these findings highlight the importance of integrating both legal systems into a hybrid legal framework that ensures justice, legal certainty, and public benefit in supporting an inclusive and sustainable digital economic ecosystem in Indonesia.